2013
DOI: 10.1038/onc.2013.136
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Kaposi's sarcoma-associated herpesvirus (KSHV) vIL-6 and HIV-1 Nef protein in promotion of angiogenesis and oncogenesis: role of the AKT signaling pathway

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the cause of Kaposi's sarcoma (KS), which is the most common AIDS-associated malignancy. KS is characterized by neovascularization and spindle cell proliferation. The interaction between HIV-1 and KSHV has a central role in promoting the aggressive manifestations of KS in AIDS patients; however, the pathogenesis underlying AIDS-related KS (AIDS-KS) remains unknown. Herein, we examined the potential of HIV-1 negative factor (Nef) to impact KSHV viral interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
86
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 59 publications
3
86
0
1
Order By: Relevance
“…vIL6 expression can also induce growth in mouse hybridoma (Hideshima et al, 2000), PEL (Chatterjee, Osborne, Bestetti, Chang, & Moore, 2002; Jones et al, 1999), BAF (Hu & Nicholas, 2006), and Hep3B hepatoma (Nicholas et al, 1997) cell lines. In endothelial cells, vIL6 expression induces proliferation, tubule formation, and neoangiogenesis (Zhou et al, 2013; Zhu et al, 2013). Additionally, vIL6 can help cells escape interferon (IFN)-induced growth arrest (Chatterjee et al, 2002).…”
Section: Lytic Kshv Proteins Involved In Cell Growth and Survivalmentioning
confidence: 99%
“…vIL6 expression can also induce growth in mouse hybridoma (Hideshima et al, 2000), PEL (Chatterjee, Osborne, Bestetti, Chang, & Moore, 2002; Jones et al, 1999), BAF (Hu & Nicholas, 2006), and Hep3B hepatoma (Nicholas et al, 1997) cell lines. In endothelial cells, vIL6 expression induces proliferation, tubule formation, and neoangiogenesis (Zhou et al, 2013; Zhu et al, 2013). Additionally, vIL6 can help cells escape interferon (IFN)-induced growth arrest (Chatterjee et al, 2002).…”
Section: Lytic Kshv Proteins Involved In Cell Growth and Survivalmentioning
confidence: 99%
“…Recently, we and others have demonstrated that Tat can not only trigger KSHV reactivation from latency (21) but also accelerate tumor progression induced by KSHV-encoded oncoproteins, including the viral G protein-coupled receptor (vGPCR), kaposin A, viral interleukin-6 (vIL- 6), and open reading frame (ORF) K1 (22)(23)(24)(25). Moreover, we have found that soluble Nef can be readily internalized by PEL cells and endothelial cells, and both soluble and ectopic expressions of Nef promote KSHV latency by inhibiting viral replication and induce angiogenesis and oncogenesis by cooperating with KSHV vIL-6 or ORF K1 (26)(27)(28).…”
mentioning
confidence: 99%
“…Much of the work done on angiogenesis has been in the context of Kaposi sarcoma, an angioproliferative mesenchymal cancer often seen in AIDS and other immune deficient patients. HIV Tat and nef have been shown to promote Kaposi sarcoma induced angiogenesis (Zhou et al 2013(Zhou et al , 2014. The anti-angiogenic factor thrombospondin-1 inhibits HIV-Kaposi sarcoma induced angiogenic activity (Taraboletti et al 1999).…”
mentioning
confidence: 99%